OPERATIONAL OPTIMIZATION OF COAL HANDLING FACILITY USING THEORY OF CONSTRAINT (TOC) AND STOCK AND FLOW MODELS - Azizul Amri; Nur Budi Mulyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Coal remains one of the most cost-effective energy sources, playing a crucial role in Indonesia's national energy mix and making a significant contribution to national revenue. PT XYZ, a leading coal producer, recorded a total production of 41.94 million tons in 2023, with coal transportation reaching 32.42 million tons. For 2026, PT XYZ has set an ambitious target of producing and delivering 60 million tons. This projected increase in annual shipment volume is expected to place considerable pressure on PT XYZ's existing heavy equipment, particularly the Load Out system at the Coal Handling Facility (CHF). The current Load Out system at CHF 3, with a nominal capacity of 1,500 tons per hour (TpH) for each conveyor, is already operating near its maximum capacity. However, this capacity is projected to be insufficient to meet the 2026 target of 10 million tons, especially as demand continues to rise towards 2030 and beyond. As coal production and transportation demands increase, it is essential to assess whether the existing infrastructure can sustain this load without compromising operational efficiency or reliability. This study employs a supply chain capability analysis method, focusing on coal transportation logistics at Train Loading Station 3 (TLS103). The key findings highlight the need for strategic enhancements to the Loading system at CHF 3, particularly in increasing conveyor capacity and optimizing the operational configuration of TLS103. Through the calculation of the required tonnage per hour (TpH) needed to achieve the 2026 production target, this study identifies significant gaps in the current system that could hinder PT XYZ's ability to meet its goals. The results of this research will serve as recommendations for decision-making regarding capital investments and operational improvements.